Projection of HIV prevalence among individuals aged 15-49 years in Chile using Holt’s double exponential smoothing model - Dr. Smartson. P. NYONI; Thabani NYONI (Zien Journals, 2024)
This study uses annual time series data of HIV prevalence among individuals aged 15-49 years for Chile from 1990 to 2020 to predict future trends of HIV prevalence over the period 2021 to 2030. The study utilizes Holt’s double exponential smoothing model. The optimal values of smoothing constants α and β are 0.6 and 0.1 respectively based on minimum MSE. The results of the study indicate that annual HIV prevalence among individuals aged 15-49 years will continue on an upward trend over the out of sample period. Therefore, we encourage authorities to scale up demand generation for all HIV services especially among key populations and vulnerable groups.
Keywords: Exponential smoothing; Forecasting; HIV prevalence